EKSPLORASI SUMBER BELAJAR DALAM PEMBELAJARAN DI SEKOLAH DASAR - Ketut Bali Sastrawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
One sign that someone has learned is a change in behavior in that person that may becaused by a change in the level of knowledge, skills, and attitude. This conscious activity is alsocarried out in every educational practice in Indonesia. As stated in the 1945 Constitution,education is one of the pillars of the creation of national intelligence. Therefore, learning as aconscious form of business can be done anytime and anywhere. It takes a form of real realizationto be able to support and improve the quality of student learning. The form of business that isintended can be in the form of optimizing various learning resources related to the subjectmatter to be delivered to elementary school students in particular. Learning resources areeverything that is around the learning environment that can be functionally used to help optimizelearning outcomes. If learning resources are classified according to the type of learning resources,they are divided into messages, people, materials, equipment, engineering, and the environment.Thus learning resources will be able to increase the productivity of learning by road, provide thepossibility of learning that is more individualized, provide a more scientific basis for learning,strengthen learning, enable learning in real time, and enable the presentation of broader learning,by providing capable information penetrate geographical boundaries.Keywords: Learning, Learning Resources, Exploration